Total Alkaline Phosphatase Activity of Water in the Lakes of Barlinek-Gorzów Landscape Park (North-West Poland) - Daniszewski, Piotr (Asian Journal of Chemistry, 2014)
Water in the lakes of Barlinek-Gorzów Landscape Park were the subjects of a five-year study (2008-2012). Total alkaline phosphatase activity was determined seven times a year in these environments. The study on the water demonstrated that the top sublittoral layer (1 m) featured the highest alkaline phosphatase activity among all the analyzed zones. A study of seasonal fluctuations showed that a maximum total alkaline phosphatase activity, both in the water occurred in spring (May) and summer (July, August). Basing on this parameter no increase in eutrophication process in the lakes of Barlinek-Gorzów Landscape Park was determined in the course of a 5-year study.